EL FENÓMENO YOUTUBER Y SU EXPANSIÓN TRANSMEDIA. ANÁLISIS DEL EMPODERAMIENTO JUVENIL EN REDES SOCIALES - Dra. Tatiana HIDALGO-MARÍ,Dr. Jesús SEGARRA-SAAVEDRA (Fonseca, Journal of Communication, 2023)
This work approaches the phenomenon of youth empowerment in social media, specifically YouTube. For this, it studies the reach of the channels of the ten most important Spanish youtubers according to Social Blade, as well as the expansion and transmedia reach of his personal branding. The descriptive analysis of their channels and the latest published videos confirms the use of links to other social networks such as Facebook, Twitter and Instagram, as well as entertainment content